Traditional Values In The Tetenger Kulkul Karawitan Work - Yulianti, Dewi (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2024)
Ancestral heritage in the form of traditional Balinese communication tools made of wood or bamboo operates in banjar activities, especially those in Banjar Palak Sukawati. The strength and character of the sound produced by the kulkul inspired the idea of ​​a creative karawitan piece called “Tetenger Kulkul”. The karawitan art composition entitled “Tetenger Kulkul” is a Bebarongan Kreasi musical composition that uses the five-tone Bebarongan Gamelan as the medium. The purpose of creating this karawitan work is to transform an idea born from a traditional communication tool called kulkul and to describe the traditional values ​​contained in the use of the kulkul communication tool as outlined through traditional karawitan works. This traditional karawitan work